Study of hepatotoxins influence in vitro on basic biochemical indicators of liver functional state - Maloshtan, Liudmyla; Storozhenko, Galyna; Galuzinska, Liubov; Fylymonenko, Victoriia; Sadiq, Omar Rashid (ScienceRise: Biological Science, 2021)
An antimicrobial drug of the fluoroquinolone group, ciprofloxacin, is widely used in Ukraine. However, some researchers have noted the probable hepatotoxicity of this drug with prolonged use or use of high doses of ciprofloxacin. The aim of this study was to compare the effects of carbon tetrachloride, as a classical model of hepatocyte injury, with the effects of ciprofloxacin. The aim of the study was to investigate the biochemical parameters of the liver when simulating toxic damage to hepatocytes with carbon tetrachloride or ciprofloxacin. Materials and methods. The study was carried out on isolated rat hepatocytes, in whose culture medium carbon tetrachloride or ciprofloxacin was added. After incubation in the supernatant and cell homogenate, the activities of marker enzymes of cytolysis were determined: ALT, AST, γ-GTP, LF, LDH, DC and MDA. Results. The introduction of ciprofloxacin into the culture of hepatocytes at a concentration of LC50 caused changes in biochemical parameters similar to those caused by carbon tetrachloride. Thus, an increase in ALT, AST, γ-GTP, LF, LDH, DC and MDA was observed when CCl4 or ciprofloxacin was added to the culture. Conclusion. Incubation of rat hepatocytes with carbon tetrachloride or ciprofloxacin caused an increase in the level of enzymes and lipid peroxidation products. These parameters are indicators of gross changes in cells, which are the result of impaired keto acid formation, impaired redox reactions, impaired glycogen production